Party-Id and Money Politics in The Dynamics of The 2024 Presidential and Vice Presidential Elections in Kupang City - Frans Bertho Ricky HUMAU; Ananias Riyoan Philip JACOB; Stefanus TRIADMAJA; Philips Yuniory Nyaleson NDODA (International Journal of Environmental, Sustainability, and Social Science, 2025)
The weakening of party identification has become a unique phenomenon from year to year, in the context of elections this weakening has caused several negative effects, one of which is the practice of money politics that is increasingly massive in society. In other words, strong party identification will reduce the practice of money politics. This hypothesis will be tried to be proven by this research by looking at the influence of party identification on money politics that occurs in the community, especially in the Presidential and Vice Presidential Elections in Kupang City in 2024. The method used in this study is a quantitative method using a survey technique of 440 respondents spread across six sub-districts in Kupang City. The conclusion obtained in this study is that party identification does not have a positive impact on public acceptance of money politics. The weak identification of parties in Kupang City is caused by the structure and institutionalization of political parties that are not running optimally. On the other hand, the people of Kupang City tend to prioritize a person's character rather than party identification. The results of the 2024 election again prove that the identification of community parties in Kupang City is still quite low.